PENERAPAN KELAS INKLUSI MELALUI PENDAMPING GURU SHADOW UNTUK MENINGKATKAN PRESTASI SISWA ABK DI SEKOLAH KRAETIF SD MUHAMMADIYAH 20 SUARABAYA - Harun Abdullah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Inclusive education might become a solution for students with special needs. Its regular curriculum can help children with special needs overcome the challenges they face in social and environmental interactions. The first problem formulation of this thesis was the inclusive classes implementation through shadow teachers to improve the learning achievement of students with special needs at SD Kreatif Muhammadiyah 20 Surabaya. The second was the achievement of students with special needs through shadow teacher assistants to improve their achievement at SD Kreatif Muhammadiyah 20 Surabaya. The third was supporting and inhibiting factors for implementing inclusive classes through shadow teachers to enhance student achievement with special needs at SD Kreatif Muhammadiyah 20 Surabaya. For this problem, researchers used qualitative research with a descriptive approach. It meant taking information from informants by using interviews, observations, and documentation as data. The conclusion from this study was that the implementation of the inclusion class at SD Kreatif Muhammadiyah 20 Surabaya was a full-normal inclusion and was quite good because it conforms to educational standards. Their achievements varied before and after shadowing. The supporting factors were a good collaboration from all parties, while the inhibiting factor was the lack of infrastructure.